THE ACUTE EFFECTS OF EXERCISE ON POST-EXERCISE INFLAMMATION AND IRON REGULATION: A COMPARISON BETWEEN TRAINED AND UNTRAINED MEN. Issue 17 (24th October 2013) - Zwygart, KA; Howe, C; Moir, HJ
Abstract : This study examined whether the magnitude of the effects of an exercise bout on inflammatory markers and iron regulation in humans differs between trained and untrained men. Changes in cell count (red blood cell, white blood cell, haemoglobin, haematocrit, lymphocytes, monocytes, granulocytes) Interleukin-6 (IL-6) and serum iron in response to a running bout were compared between both groups. Seven untrained (VO2max 47.4±4.1 ml·kg −1 ·min −1 ) and seven trained (56.9±4.5 ml·kg −1 ·min −1 ) men aged 19–48 years completed a Bruce protocol treadmill test and a subsequent treadmill run (45 min at 75% of VO2max ). Ethical approval was granted by Kingston University Faculty Ethics Committee and conducted in accordance to the Declaration of Helsinki. Venous whole blood was collected before, and at 0, 3, 6 and 24 after exercise. Exercise-induced plasma volume changes were accounted for. Mixed Model ANOVA was performed to examine differences within groups. Independent t-tests identified which time points differed between groups, and dependent t-tests were applied to examine changes within groups over time. Significance was accepted at P <0.05. Differences between groups were observed for haemoglobin ( P <0.005) and red blood cell ( P =0.007) at all time points, as well as for haematocrit at all time points except at baseline ( P =0.013). Lymphocytes, Monocytes, Granulocytes, IL-6 and iron levels did not differ between groups. IL-6 levels were increased post-exercise in both groups, and iron was different 3 h post-exercise to 6 h post-exercise ( P <0.05). Findings suggest haemoglobin, haematocrit and red bloods to be lower in trained individuals due to adaptations of endurance training. The single exercise running bout elicited an acute inflammatory response represented by an increase in IL-6 and decrease in serum iron. Alterations in IL-6 were not different between trained and untrained men, indicating a lack of effect of training status.